(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The actions of companies are a multifaceted and complex procedure. The company communicates with several factors at various levels, from state to the suppliers. At the same time, in the course of the organization’s whole operation, both internal and external ever-changing circumstances impact its actions and performance. That kind of ever-changing ambiance places organizations at risk of an financially unstable position. A company’s bankruptcy is a regarded as crisis that needs particular approaches of financial management to surmount that. It appears greatly significant to evaluate the status of the company, take steps to restore solvency, and define the likelihood of bankruptcy. Analysis and assessment of the likelihood of bankruptcy supply an overall evaluation of the company’s monetary stability, and a prediction for the future. This study aims to analyze some practical means to forecast companies’ potential bankruptcy and financial insolvency. To gratify that aim, monographic, economic-statistical, and abstract-logical methods are considered. Based on the results obtained, to raise the effectiveness of the company’s capital, working capital should be normalized through planning the lowest requirement for working capital for all the constituent factors vital for the company’s uninterrupted, and normal operation.